2016
DOI: 10.1093/nutrit/nuv064
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, metabolism, and functions of β-cryptoxanthin

Abstract: β-Cryptoxanthin, a carotenoid found in fruits and vegetables such as tangerines, red peppers, and pumpkin, has several functions important for human health. Most evidence from observational, in vitro, animal model, and human studies suggests that β-cryptoxanthin has relatively high bioavailability from its common food sources, to the extent that some β-cryptoxanthin-rich foods might be equivalent to β-carotene-rich foods as sources of retinol. β-Cryptoxanthin is an antioxidant in vitro and appears to be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 147 publications
(297 reference statements)
2
107
0
2
Order By: Relevance
“…Of several carotenoids identified in peel and pulp of citrus extracts, β-cryptoxanthin, which was detected in some of the citrus sample extracts, is remarkably interesting due to its high bioavailability in human metabolism. Different studies also showed that β-cryptoxanthin has a better bioavailability compared to β-carotene [40]. Moreover, β-cryptoxanthin is a well-known vitamin A precursor, and has been linked with the ability to delay osteoporosis and to prevent certain types of cancers [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of several carotenoids identified in peel and pulp of citrus extracts, β-cryptoxanthin, which was detected in some of the citrus sample extracts, is remarkably interesting due to its high bioavailability in human metabolism. Different studies also showed that β-cryptoxanthin has a better bioavailability compared to β-carotene [40]. Moreover, β-cryptoxanthin is a well-known vitamin A precursor, and has been linked with the ability to delay osteoporosis and to prevent certain types of cancers [40].…”
Section: Resultsmentioning
confidence: 99%
“…Different studies also showed that β-cryptoxanthin has a better bioavailability compared to β-carotene [40]. Moreover, β-cryptoxanthin is a well-known vitamin A precursor, and has been linked with the ability to delay osteoporosis and to prevent certain types of cancers [40]. In a country with a substandard health care system as Indonesia, knowledge of beneficial nutrition with preventive potency will be very useful.…”
Section: Resultsmentioning
confidence: 99%
“…Because visceral fat, which is better measured by WC than BMI , is more metabolically active and likely responsible for much of the adverse effects of excess adiposity , this result suggests that the lower levels of these metabolites may contribute to obesity‐related diseases. β‐cryptoxanthin is an oxygenated carotenoid that is abundant in blood and can act as an antioxidant . The plasmalogens, which have a vinyl ether‐linked alkyl chain in the sn‐2 position, can also act as antioxidants .…”
Section: Discussionmentioning
confidence: 99%
“…Only one OH group was added to β-cryptoxanthin. Although β-carotene is present in large quantities in a large number of fruits and vegetables, β-cryptoxanthin is present in small number of food sources but at high concentrations [42].…”
Section: β-Cryptoxanthin Is a Natural Carotenoid Pigment β-Cryptoxanmentioning
confidence: 99%